Temporal dynamics and species-level complexity of Prevotella spp. in the human gut microbiota: implications for enterotypes and health - Han, Na; Peng, Xianhui; Zhang, Tingting; Qiang, Yujun; Li, Xiuwen; Zhang, Wen (Frontiers in Microbiology, 2024)
The concept of "enterotypes" in microbiome research has attracted substantial interest, particularly focusing on Prevotella spp. abundance in the human gut. Here, the intricate dynamics of Prevotella spp. within the human gut microbiota was investigated based on metagenomic method. First, 239 fecal samples from individuals across four regions of China revealed a bimodal distribution, highlighting the variability in Prevotella spp. abundance within the Chinese population. Secondly, a longitudinal cohort study includes 184 fecal samples from 52 time points collected from seven individuals demonstrated outbreaks or disappearances of Prevotella spp., emphasizing the transient nature of Prevotella abundance levels and suggesting shifts in Prevotella "enterotypes". Additionally, a turnover of the dominant Prevotella spp. was observed, indicating the potential presence of diverse Prevotella enterotype subtypes. Notably, genomic analysis, which demonstrated the persistence of specific Prevotella strains within individuals over extended periods, underscores the enduring presence of Prevotella in the human gut. In conclusion, by integrating temporal and geographical scales in our research, we gained deeper insights into Prevotella dynamics, emphasizing the importance of considering time-and species-level dynamics in gut microbiota studies and their implications for human health.